Performance of indigenous and exotic clones of rubber in india - John, Alice; Varghese, Y. Annamma; K. Mushrif, Sadanand (Journal of Plantation Crops, 2009)
Twelve clones of rubber (Hevea brasiliensis) (RRII 5, RRII 118, RRII 208, RRII 300, RRII 308, RRIM 600, RRIM 703, PR 255, PR 261, SCATC 88-13, SCATC 93-114 and Haiken 1) of which three are Chinese clones were evaluated in a large scale trial along with the control clone RRII 105. The trial was laid out in 1989 and the trees were opened for tapping during the 7th year after planting in 1996. The performance of these clones with respect to yield over a period of nine years, growth attributes, timber traits, incidence of tapping panel dryness, Phytophthora, pink and powdery mildew disease are presented. Significant clonal variations existed for all the characters. Clone RRII 5 (66.02 g/t/t) was the highest yielder over nine years of tapping followed by RRII 118 (54.55g/t/t), RRII 308 (47.27 g/t/t) and RRII 208 (46.77 g/t/t). Clone RRII 118 showed a rising yield trend. Among the cold tolerant Chinese clones evaluated SCATC 88-13 (45.00 g/t/t) showed comparable yield while SCATC 93-114 was the best in terms of growth and secondary attributes. Superiority of clones for specific traits is discussed.